2020
DOI: 10.3390/v13010030
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Novel Reassortant H1N1 Avian Influenza Viruses in Korean Wild Ducks in 2018 and 2019

Abstract: Influenza A virus subtype H1N1 has caused global pandemics like the “Spanish flu” in 1918 and the 2009 H1N1 pandemic several times. H1N1 remains in circulation and survives in multiple animal sources, including wild birds. Surveillance during the winter of 2018–2019 in Korea revealed two H1N1 isolates in samples collected from wild bird feces: KNU18-64 (A/Greater white-fronted goose/South Korea/KNU18-64/2018(H1N1)) and WKU19-4 (A/wild bird/South Korea/WKU19-4/2019(H1N1)). Phylogenetic analysis indicated that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The T97I substitution in the PA protein has been proven to enhance polymerase activity and virulence ( Yang et al, 2019 ); however, we did not detect the 97I mutation in any of the six H3N2 strains. H9N2 AIV has been the dominant AIV and the dominant epidemic AIV in China for a long time, and the 195K mutation in PA-X amino acids has been proven to enhance the virulence of H9N2 AIV in mammals in previous studies ( Sun et al, 2020 ; Trinh et al, 2020 ). All the identified strains in this study have this substitution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T97I substitution in the PA protein has been proven to enhance polymerase activity and virulence ( Yang et al, 2019 ); however, we did not detect the 97I mutation in any of the six H3N2 strains. H9N2 AIV has been the dominant AIV and the dominant epidemic AIV in China for a long time, and the 195K mutation in PA-X amino acids has been proven to enhance the virulence of H9N2 AIV in mammals in previous studies ( Sun et al, 2020 ; Trinh et al, 2020 ). All the identified strains in this study have this substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, all six H3N2 viruses have a P/A42S mutation in the NS1 protein, which is associated with increased virulence in mammalian hosts ( Tuong et al, 2020 ). The M31I substitution in the NS2 protein is thought to be associated with increased virulence in mammals ( Trinh et al, 2020 ). However, our isolates did not contain this mutation, which indicated that these strains might have low virulence in mammals.…”
Section: Resultsmentioning
confidence: 99%
“…The open reading frame (ORF) was observed using the obtained consensus and adopted a result with an ORF similar to the reference. As the ORF length differed from the reference, sequence error was corrected using Proof Read as previously described [19].…”
Section: Next Generation Sequencing (Ngs) By Illumina Hiseq X Methodsmentioning
confidence: 99%
“…During this severe pandemic of 1918, about 500 million (about one-third of the world population) contracted the virus, and between fifty to hundred million people were reported to be killed [ 24 ]. Avian H1N1 viruses entered the swine population of Eurasia and were reported to be co-circulating with classical swine flu viruses in 1979 [ 25 ]. An H1N1 strain that swept through India in 2015 resulted in around 10,000 incidents and 774 mortalities [ 24 ].…”
Section: Epidemiology Of Avian Influenza Virusesmentioning
confidence: 99%